Pelatihan Kewirausahaan dalam Meningkatkan Wawasan dan Keterampilan Berwirausaha Bagi Warga di Kelurahan Padang Harapan Kota Bengkulu - Dedi Supriyadi; Mas Agus Firmansyah; Neneng Cucu Marlina (JURNAL ABDIMAS SERAWAI, 2022)
The purpose of community service, in general, is to improve the knowledge, skills and attitudes of the target participants, as well as to develop one's talents, to perform the work as required. The purpose of this service is 1) to increase the insight and knowledge of citizens to have the ability to fill or capture entrepreneurship opportunities for the community of RT. 012/RW. 04 in Kelurahan Padang Harapan, Kecamatan Gading Cempaka in Bengkulu City; 2) to improve skills more effectively to produce better and faster creative products/services in the community of RT. 012/RW. 04 Kelurahan Padang Harapan, Kecamatan Gading Cempaka of Bengkulu City; 3) To develop leadership attitudes, self-reliance behavior, then by itself will cause the willingness to build networking (network cooperation) with other parties. Method of this community service starting from (1) Socialization to the head of RT and the community; (2) Training in the form of extension of insight and entrepreneurial knowledge followed by discussion; (3) The practice of making ginger-based products. Considering the theme of this ginger process, ginger is easy to find in Bengkulu, and the market is relatively easy. The variables measured are improvements in insight, knowledge, skills, attitude or response to activities. There is an increase in participants' insights from some questions at the beginning of the activity (pre-test). Before, the participants' answers were almost identical: that entrepreneurship is synonymous with selling practically. After being given knowledge about entrepreneurship, reevaluated (post-test) with the same question, the answers have changed their insights about knowledge and attitudes to entrepreneurship. According to them, not only as sellers or traders, but other fields of services that depend on the purpose of entrepreneurship are to obtain profits in the form of economic materials and benefits in the form of entrepreneurial insights